Health and Wellness in the Age of Digital Landscapes: Fostering Quality of Life - Bhupinder Singh (International Journal of Trends in Humanities, 2025)
Digital technologies have been transforming the world of health and wellness, bringing unique ways to enhance people's life quality around grand scale. These developments are completely changing the way we think about social health, mental health, and physical fitness. People can better monitor, manage, and optimize their health by utilizing technologies like wearables, telemedicine, and smartphone health apps in conjunction with artificial intelligence. This study examines the various ways that digital tools might support health and wellness, looking at how they affect adoption rates, service accessibility, and health outcomes. Additionally, by enhancing connectivity and providing real-time support, these technologies have the ability to close healthcare gaps, particularly in underprivileged areas. The study also discusses important issues related to the digital health revolution, like data privacy issues, the necessity of strong cybersecurity defenses, and the significance of encouraging users' digital literacy. It emphasizes how important it is for governments, medical professionals, and tech companies to work together to build a fair and inclusive digital health environment. In the end, this study makes the case that a comprehensive digital environment may support global wellness systems, improving personal wellbeing and opening the door for universal access to affordable, sustainable healthcare.
Keywords: Health and Wellness; Quality of life; Telemedicine; digital landscapes; digital literacy